The Effect of Accounting Information Systems and Internal Control of Employee Performance - Friska Zagita Sagala (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study learns to study the existence of accounting information systems and internal controls on employee performance. The population of this study is the company part of the Internal Control Unit, Business and Product Development, Broadband SBU, Corporate Finance, and HCM & Quality at PT. INTI Persero Bandung. The sampling technique in this study used a purposive sampling method of 43 respondents consisting of managers and part staff of the Internal Control Unit, Business and Product Development, Broadband SBU, Corporate Finance, HCM & Quality. The data used using primary data and data analysis methods in this study are descriptive methods and verification methods using quantitative. The technique of collecting data is by distributing questionnaires directly to PT. Persero Persero. The statistical test tool used in this study is the classic Assumption Test, Multiple Linear Regression Test, Coefficient coefficient analysis test, Test coefficient of determination and t test The results of this study prove that: 1) Accounting Information Systems against Employee Performance, 2) Internal Control affects Employee Performance.